Strategi Pemberdayaan Sentra Industri Konveksi Dalam Upaya Meningkatkan Kesejahteraan Masyarakat Di Desa Tritunggal Kecamatan Babat Kabupaten Lamongan - Putri Maisarohtussa’diyah; Muhammad Ridwan Basalamah; Satria Putra Utama (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The strategy for empowering the convection industry center in an effort to improve the welfare of the people in Tritunggal Village is as well as empowering the convection industry center to improve people's welfare, through human resources in the environment around Tritunggal Village. Tritunggal Village, Babat District, Lamongan Regency is one of the locations with quite a lot and adequate convection industrial centers. With a total of 154 convection industry businesses as of February 24 2022, as well as the production of children to adult clothing, uniforms, screen printing and embroidery that have been made or received to order. Focusing on the middle-class convection industry center named